Increasing evenness in the neighbourhood distribution of income poverty in England 2005–2014: Age differences and the influence of private rented housing. (March 2019) - Fransham, Mark
A recent change in the geography of poverty in Britain has been reported: it appears to be becoming more evenly distributed in major cities, such that low-income individuals are less likely to be living in the highest poverty areas. Studying all local authority areas in England between 2005 and 2014, this paper finds that this phenomenon is strongly differentiated by age group and local authority type. Poverty amongst children and working age people is becoming more evenly distributed in almost all local authority types, with the largest changes occurring in the most urban areas. The change is strongly associated with the increasing proportion of low-income households living in private sector housing. Conversely, there is evidence of an increasing residential concentration of poverty at older ages. The paper also proposes a method for decomposing a change in rates between changes in the numerator and changes in the denominator. It concludes by discussing the implications of these findings for area effects, area-based initiatives and gentrification by displacement.